Pengujian dan Analisa Pilihan Jenis Pasir Terbaik dari Desa Payo, Desa kebur, dan Desa Gunung Agung Kabupaten Lahat Melalui Pengujian Kuat Tekan Beton Mutu K-250 - RR. Susi Riwayati; Delli Noviarti Rachman; Rivo Supriza Rasandes (Jurnal Tekno Global, 2021)
One of the constituents of concrete is sand. Good sand for concrete material is one that has a certain size, sharpness and sharpness so that it can bind to each other. South Sumatra, where every city and district is traversed by major rivers, of course has an abundant and sufficient supply of sand material to fulfill development in the South Sumatra region. One of the largest sand-producing areas in the South Sumatra region is the one from Lahat Regency. Sand from Lahat Regency comes from the Lematang River. All locations in the Regency are traversed by the Lematang River, one of which is the West Merapi District. West Merapi District is one of the suppliers of sand for the surrounding districts, including the city of Palembang. Unlike the sand from Ogan Ilir, the sand from West Merapi is more famous for its quality. For this reason, the author is interested in raising local wealth in this West Merapi District. There are 3 largest sand-producing villages in the West Merapi area, namely Kebur Village, Payo Village and Gunung Kembang Village. The author took 3 samples of sand from the three villages in order to know which village was the best. Based on the results of testing in the laboratory, it was found that the concrete product with sand from Payo village is the best, because it has a compressive strength above 260 kg/cm2. Keywords : Local materials, K-250 Quality Concrete, sand, Desa Payo, Desa Kebur, Desa Gunung Kembang.